Bulgaria : Fourth Review Under the Stand-By Arrangement, Requests for Waiver of Applicability of Performance Criteria and Waiver of Nonobservance of Performance Criterion, and Request for Extension of the Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
Bulgaria's macroeconomic performance in the face of the prolonged slowdown in the EU has been impressive, but risks have intensified. The response of fiscal policy to these risks has been adequate. Plans to increase reliance on state enterprises to carry out public sector activities are worrying. The government has taken the right approach to addressing the rapid growth in private sector credit. Bulgaria has made good progress on its structural reform agenda, but an intensified effort is required to help deal with greater macroeconomic risks.